(untitled) (Nativa, 2024)
Demand for organic food has increased as a result of awareness of the health risks posed by the presence of chemical residues. In this context, this study aimed to verify the safety of lettuce (Lactuca sativa) and arugula (Eruca sativa) produced organically in the metropolitan region of Cuiabá, MT, Brazil, and identify the main microbiological contamination sources of this production system. Fifty-five samples, 10 lettuces and 10 arugula, were collected in a farm and supermarket, in addition to five samples of each agricultural adjuvant used in the production system (irrigation water, vegetable and animal fertilizers). No Salmonella spp. was detected, although thermotolerant coliforms above the maximum acceptable limit established by the Commission on Microbiological Specifications for Foods (ICMSF) were observed in 90% (9/10) and 50% (5/10) of the farm arugula and lettuce samples, 20% (2/10) and 10% (1/10) of the supermarket arugula and lettuce samples, 60% of animal and vegetable fertilizers (6/10) and 40% (2/5) of irrigation water samples. Over half of the vegetable samples analyzed herein were, thus, unfit for consumption, indicating the relatively high influence of system inputs on the hygienic-sanitary quality of the arugula and lettuce produced in the investigated organic farm. Keywords: fertilization; organic farming; sanitary quality; contamination. Qualidade higiênico-sanitária de alface (Lactuca sativa) e rúcula (Eruca sativa) produzidas em sistema de produção orgânica em Cuiabá, MT, Brasil RESUMO: A procura por alimentos orgânicos tem aumentado devido a conscientização sobre os riscos à saúde decorrentes da presença de resíduos químicos. Nesse contexto, este estudo teve como objetivo verificar a segurança de alface (Lactuca sativa) e rúcula (Eruca sativa) produzidas organicamente na região metropolitana de Cuiabá, MT, Brasil, e identificar as principais fontes de contaminação microbiológica desse sistema de produção. Cinquenta e cinco amostras, sendo 10 de alfaces e 10 de rúculas foram coletadas em uma fazenda e supermercado, além de quinze amostras de adjuvantes agrícola utilizados no sistema de produção. Nenhuma Salmonella spp. foi detectada, embora coliformes termotolerantes acima do limite máximo aceitável estabelecido pela Comissão de Especificações Microbiológicas para Alimentos (ICMSF) tenham sido observados em 90% (9/10) e 50% (5/10) das amostras de rúcula e alface da fazenda, 20 % (2/10) e 10% (1/10) das amostras de rúcula e alface de supermercado, 60% de fertilizantes animais e vegetais (6/10) e 40% (2/5) de amostras de água de irrigação. Mais da metade das amostras de hortaliças aqui analisadas estavam, portanto, impróprias para consumo, indicando a influência relativamente alta dos insumos do sistema na qualidade higiênico-sanitária da rúcula e alface produzidas na fazenda orgânica investigada. Palavras-chave: fertilização; agricultura orgânica; qualidade sanitária; contaminação.